Еволюція культурного статусу підприємців у другій половині ХІХ – початку ХХ ст. (на прикладі колекціонера П. І. Харитоненка) - Гайдай, О.М. (Історичний архів. Наукові студії, 2015)
Мета статті – показати еволюцію культурного статусу підприємців, перехід від кількісного до якісного складу колекцій, естетичну та історико-художню значущість приватних зібрань на прикладі колекціонера П. І. Харитоненка.
Індивідуальність колекціонера формує система естетичних цінностей. З другої половини XIX ст. на мистецькому ринку і в принципах колекціонування відбуваються суттєві зміни. Торгово-промислова буржуазія впливала не тільки на економічний розвиток країни, вона внесла неоціненний внесок у розвиток культури. Приватна колекція П. Харитоненка унікальна й неповторна. Вона містить персоніфіковані риси, які визначаються індивідуальними вподобаннями збирача. У збереженні історико-культурних пам’яток, ув популяризації мистецтва цукрозаводчику Павлу Івановичу Харитоненку належить визначна роль. Безумовно, приватна колекція була не лише можливістю для збереження матеріальних предметів, що відображали духовну культуру, вдалим вкладенням капіталу в збирання предметів, але й нагодою підвищити культурний статус підприємців-колекціонерів. Цель статьи – показать эволюцию культурного статуса предпринимателей, переход от количественного к качественному составу коллекций, эстетическую и историко-художественную значимость частных собраний на примере коллекционера П. И. Харитоненко. Индивидуальность коллекционера формирует система эстетических ценностей. Со второй половины XIX в. на художественном рынке и в принципах коллекционирования происходят существенные изменения. Торгово-промышленная буржуазия, влияла не только на экономическое развитие страны, она внесла неоценимый вклад в развитие культуры. Частная коллекция П. Харитоненко уникальная и неповторимая. Она содержит персонифицированные черты, которые определяются индивидуальными предпочтениями собирателя. В сохранении историко-культурных памятников, популяризации искусства сахарозаводчику Павлу Ивановичу Харитоненко принадлежит выдающаяся роль. Безусловно, частная коллекция была не только возможностью для сохранения материальных предметов, которые отражали духовную культуру, удачным вложением капитала в собирание предметов искусства, но и возможностью повысить культурный статус предпринимателей-коллекционеров. The article aims to show the evolution of the cultural status of entrepreneurs, the transition from the quantitative to the qualitative composition of the collections, the aesthetic and art-historical significance of private collections on the example collector P. I. Kharitonenko. The great important of Russia creation of the cultural heritage is studying the experience of previous generations. The individuality of the collector forms a system of aesthetic values. Since the second half of the XIX century on the art market and in the principles of collecting is changing. Commercial and industrial bourgeoisie, had an influence not only on the economic development of the country, it has made an invaluable contribution to the development of culture. In the second half of XIX – beginning of XX century most of the Ukrainian lands were part of the Russian Empire. All ownership of Kharitonenko family was closely connected with sugar factory activity. Together with the Kiev «sugar kings» Tereshenki with Kharitonenko actually kept under control all the sugar market – from production and processing to sales. Private collection of P. Kharitonenko was unique. It contains personalized traits that are determined by the individual preference of the collector. P. Kharitonenko had a collection of Russian and West-European paintings, as well as gathered a large collection of icons. Research activities P. Kharitonenko in the light of studying the problem of the evolution of the cultural status of entrepreneurs in the second half of XIX – early XX century, has never previously been the subject of scholarly circles. The emergence of a new economic class of factory owners, factory owners, bankers begins to form and a new type of collectors. This was a collector of works of art and objects that trusted their own taste more than the opinions and recommendations of authorities. Collection individuals were not similar, the selection time was on their own and reflect the state of mind of the owner. To the sugar magnate Pavel Ivanovich Kharitonenko belongs to a the important role of the preservation of historical and cultural monuments and the popularization of art. Of course, private collection was not only an opportunity for the preservation of material objects that reflect spiritual culture, a good investment in gathering objects but also to raise the cultural status of entrepreneurs, collectors.